CTX-M β-lactamases and associated integrons: their dissemination in Gram-negative bacteria - Dimude, Juachi (The University of Edinburgh, 2013)
Gram-negative bacteria are able to cause many infections including blood stream infections (BSI).These bacteria may become resistant to antibiotics, often by acquiring genes in the presence of antibiotic selection pressure. Multi drug resistant Gram-negative bacteria have become an increasing problem worldwide. A study of antibiotic resistance in Gram-negative bacteria isolated from blood cultures from patients in the New Royal Infirmary of Edinburgh (NRIE) was performed. In addition, a study was performed on isolates from patients in an intensive care unit in Egypt. All isolates were investigated for susceptibility to an extensive range of antibiotics. Gram-negative bacteria from Edinburgh found to be resistant to either cefotaxime or ceftazidime were investigated further. Among the cefotaxime/ceftazidime resistant isolates, Polymerase Chain Reaction (PCR) analysis revealed the presence of CTX-M- β-lactamases. Seven E.coli isolates were found to have CTX-M-15 β-lactamases while the CTX-M-14 β-lactamase was detected in six Enterobacter cloacae. The insertion sequence ISEcp1 was detected upstream of the blaCTX-M-15 gene in some isolates while IS26 was found truncating the ISEcp1 in other isolates. Conjugation experiments found the blaCTX-M-15 gene was transferable to E. coli J62-2. All the isolates had detectable plasmids, a plasmid ~260kb carried the blaCTX-M-15 gene. Analysis of the -containing isolates by PFGE shows that those carrying the CTX-M-14 β-lactamase were identical indicating cross infection within the hospital. The CTX-M- 15 β-lactamase-containing isolates showed four isolates had ≥85% similarity but the others were diverse. Class 1 integrons were found in eight of the CTX-M β-lactamase containing isolates with the associated gene cassette and sul1 gene. The isolates from Egypt were found to be resistant to carbapenem, which is the final mainstream antibiotic option in the treatment of multidrug resistant Gram-negative bacteria. Further analysis revealed all carried the CTX-M-14 β-lactamase and two additionally carried the VIM-4 metallo β-lactamase, which accounted for the resistance to the carbapenems. Furthermore, the insertion sequence ISEcp1 was found upstream of the blaCTX-M-14 gene in two of the isolates. The blaVIM-4 gene was found to be part of the gene cassette in the class 1 integron associate with complex ISCR1. Two of the Egyptian isolates had a detectable plasmid, ~300kb in size, which carried both blaCTX-M-14 and blaVIM-4 genes. All the blood culture isolates were examined to ascertain the persistence of sulphonamide resistance despite the long-term prescribing reduction on this antibacterial. PCR was performed to detect sul1, sul2 and sul3 genes in all the isolates. Of the sulphonamide resistant isolates 25 carried the sul1, 27 carried the sul2 and none carried the sul3 genes. Eight isolates had both the sul1 and sul2 genes. Most of the isolates carried sul1 had Int1 as part of the same class 1 integron. Interestingly three isolates were PCR negative for sul1 but positive for sul2 and int1. Int2 and 3 were found in 3 and 2 isolates respectively. The class 1 integron contained different insert gene cassettes; dfrA (dfrA17, dfrA16, dfrA15), aadA (aadA5, aadA2, aadA1) and blaOXA-1 families in addition to the resident sul gene. In conclusion this thesis shows the diversity of the genetic environment and carriers of the CTX-M β-lactamases within the same hospital. Sulphonamide resistance in Gram-negatives persists despite the prescribing reduction of this antibacterial in a Scottish hospital and the recommended constraint on the use of sulphonamide.
Keywords: CTX-M; integrons; sul genes